Implementasi Pajak di Negara-Negara Muslim (Studi Banding Negara-Negara Arab, Indonesia, dan Malaysia) - Mawftiq, Rarasati; Nugroho, Anton Priyo; Gustanto, Edo Segara (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
This study examines the implementation of taxation in Islamic countries through a comparative analysis of Arab states, Indonesia, and Malaysia. Taxation serves as a vital instrument for sustaining national budgets, yet its application differs across countries depending on economic structures, political settings, and religious considerations. In Arab states, particularly within the Gulf region, personal income tax is generally absent, as state revenues rely heavily on oil and gas resources. Instead, fiscal diversification is achieved through zakat, corporate taxation, and value-added tax (VAT). Indonesia, as the most populous Muslim-majority country, places strong reliance on taxation as the backbone of its national budget, primarily through income tax, corporate tax, and VAT, while zakat is managed by religious institutions in a complementary manner. Malaysia adopts a hybrid approach by maintaining modern tax instruments such as personal and corporate taxes while simultaneously integrating zakat management under state religious authorities, thereby harmonizing fiscal and religious obligations. The findings highlight that taxation systems in Islamic countries are not uniform but shaped by their unique socio-economic realities. Gulf states offer tax incentives with limited direct taxation, Indonesia emphasizes a progressive tax system, while Malaysia seeks to balance taxation and zakat. This comparison underscores the diversity of fiscal models in Islamic contexts and their adaptability to local conditions.